Cascade Reaction of α, β‐Unsaturated Ketones and 2‐Aminoaryl Alcohols for the Synthesis of 3‐Acylquinolines by a Copper Nanocatalyst. Issue 18 (4th August 2021) - Liu, Yuan; Wang, Chen; Tong, Yixin; Ling, Yong; Zhou, Changjian; Xiong, Biao
Abstract: 3‐Acylquinolines possess widespread applications in functional chemicals. However, the convenient and selective synthesis of such important substructures has to date remained a challenge. Herein, we report a method to access 3‐acylquinolines from α, β‐unsaturated ketones and 2‐aminoaryl alcohols in one pot with a copper nanocatalyst supported on nitrogen‐silica‐doped carbon (Cu/N−SiO2 −C). Mechanistically, the construction of the product involves a cascade procedure including radical‐type oxidation of 2‐aminoaryl alcohols, aza‐Michael addition and annulation. This developed protocol proceeds with merits of mild reaction conditions, good functional group tolerance, earth‐abundant and reusable copper catalyst, easily available stocks and O2 as the sole oxidant, which provides an alternative way for the sustainable synthesis of quinoline derivatives. Abstract :